PERBANDINGAN PROFIL FITOKIMIA DAN GCMS MENGGUNAKAN EKSTRAKSI MASERASI DAN SOKHLETASI SERTA PROFIL HISTOKIMIA DAUN SUNGKAI (P. canescens Jack.) - Jaya, Fahriza Kusuma; Fariani, Rini; Ain, Nor (Universitas Lambung Mangkurat, 2024)
Sungkai leaf (P. canescens Jack.) is a native plant of Indonesia that has long been used in traditional medicine as a mouthwash and minor wounds. Sungkai leaves P. canescens Jack. are believed by the community to have many health benefits. Several studies have shown that sungkai leaves (P. canescens Jack.) contain active compounds. As for the extraction process, it is known that the content of active compounds obtained in the sungkai leaf extract is strongly influenced by the selection of solvents used and the extraction method carried out. In previous studies, total flavonoid content has been obtained using maceration and soxhletation methods in sungkai leaf extracts, where flavonoids are one of the profiles of secondary metabolite compounds possessed by sungkai leaves. In the next research, the profile of sungkai leaves will be determined more thoroughly through phytochemical screening and GCMS analysis of the extraction results using maceration and soxhletation methods. The histochemical profile of sungkai leaves will also be determined. Histochemical test results show that flavonoid compounds are evenly distributed in all tissues of sungkai leaves, besides that some tissues in sungkai leaves show positive results for the presence of alkaloid, steroid, terpenoid, tannin, phenol and saponin compounds.The results of phytochemical screening showed that sungkai leaves positively contained secondary metabolite compounds in the form of alkaloids, flavanoids, steroids, terpenoids, tannins, phenolics, saponins while the results of GCMS analysis for the maceration process obtained metabolite compounds in the form of terpenoids, alkaloids, and phenolics, while for the sokletation process obtained metabolite compounds in the form of flavonoids, terpenoids, and phenolics.